THE EFFECT OF THE USE OF AI, LEARNING CREATIVITY, AND SELF-EFFICACY ON STUDENT LEARNING INNOVATION - Khildah Salsabilatun Najah; Munirul Abidin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to examine the effect of artificial intelligence (AI) utilization, learning creativity, and self-efficacy on students' learning innovation. A quantitative approach with a causal associative research design was employed. Data were collected through a survey involving 157 university students selected using purposive random sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that AI utilization, learning creativity, and self-efficacy have a positive and significant effect on students' learning innovation, both partially and simultaneously. Among the three independent variables, self-efficacy demonstrates the most dominant influence on learning innovation. These findings suggest that learning innovation is not only driven by technological advancement but also strongly influenced by students' psychological readiness and creative capacity. This study contributes to the integration of technological, psychological, and pedagogical perspectives in understanding learning innovation in higher education within the context of digital transformation.